18F-Sodium fluoride PET/CT detects transcatheter aortic valve degeneration. (8th February 2021) - Tzolos, E; Kwiecinski, J; Cartlidge, TRG; Fletcher, A; Doris, MK; Tarkin, JM; Slomka, PJ; Newby, DE; Rudd, JHF; Berman, DS; Dweck, MR
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): This work was supported by the British Heart Foundation, London, United Kingdom Background: Early detection of transcatheter aortic valve implantation (TAVI) degeneration is challenging and only feasible when advanced haemodynamic valve dysfunction is apparent.  Purpose: We tested whether 18F-sodium fluoride (18F-NaF) positron emission tomography and computed tomography (PET/CT) could detect structural TAVI degeneration and haemodynamic valve dysfunction.  Methods: After TAVI implantation, patients underwent baseline echocardiography, CT angiography and 18F-NaF PET/CT (Figure). We assessed for morphological changes, stenosis or regurgitation on Doppler echocardiography, CT (hypoattenuated leaflet thickening [HALT] or spotty calcification) and PET (18F-NaF uptake; maximum target-to-background ratio, TBRmax). We categorised structural valve degeneration (SVD) according to the standardised definition for surgical and transcatheter bioprosthetic valves, as proposed in a recent consensus statement.  Results: We recruited 47 patients (81 ± 6 years old, 79% male) 1 month (n = 9), 2 years (n = 22) or 5 years (n = 16) after TAVI: 25 (53%) had received a balloon expanded bioprosthesis and 22 (47%) a self-expanding valve. There was moderate valve dysfunction on Doppler echocardiography in 3 (6%) patients, HALT on CT in 6 (13%) patients, spotty calcification in one patient and 18F-NaF uptake in 7 patients (15%) (TBRmax range: 1.59-5.88); all enrolled 5 years post-TAVI. All patients with increased 18F-NaF uptake (TBRmax ≥1.59) demonstrated either SVD without haemodynamic valve dysfunction (stage 1, n = 4) or structural valve dysfunction with moderate valve dysfunction and mean transprosthetic pressure gradients >20 mmHg (stage 2, n = 3). In patients without increased 18F-NaF uptake there was no evidence of structural valve degeneration (n = 40). Within the increased 18F-NaF uptake (n = 7) group, patients with stage 2 SVD (n = 3) demonstrated higher uptake compared to patients with stage 1 SVD (TBRmax 4.3 [3.02-5.88] versus 1.8 [1.59-2.28]). Patients with stage 2 SVD (n = 3) had over 3 times higher TBRmax than those without SVD (n = 40) (4.30 [3.02, 5.88] versus 1.31 [1.21, 1.46]; p < 0.001); Figure). Conclusion: 18F-NaF PET/CT detects patients with SVD and potentially identifies those at risk of valve failure.